Roman Ingarden’s Spaces od the Word. Part 1 - Ulicka, Danuta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
The article delves into the literary oeuvre of Roman Ingarden, the prominent Polish phenomenologist, philosopher, aesthetician, and literary theorist. While his scholarly contributions are globally acknowledged, his literary output, in stark contrast, remains largely undiscovered, archived within the confines of his family collection, with only sporadic references in dispersed texts. Intriguingly, some portions of his literary creations were purportedly prepared for publication by the author himself. This corpus of work, primarily comprising poetry but also prose, drama, and autobiographical writings, unveils not only Ingarden’s artistic predilections – ranging from thematic and stylistic inclinations to genre preferences and rhythmic patterns, exhibiting clear affiliations with Young Poland’s poetry – but also provides insight into the implicit conception of subjectivity embedded in his poetic compositions. This nuanced understanding significantly supplements and reinforces the overtly articulated notion of subjectivity present in his writings addressing Edmund Husserl’s philosophy. Additionally, Ingarden’s poetic works, when juxtaposed with the poetry of his contemporaries – such as Kazimierz Twardowski, Stefania Skwarczyńska, Maria Dłuska, Roman Jakobson, and Victor Shklovsky – assumes a pivotal role as an artifact, offering a lens through which to comprehend the prevailing cultural milieu of the epoch. Simultaneously, it provokes the question of why outstanding innovators in literary studies exhibited an intriguing conservatism in their own literary endeavors.

Artykuł podejmuje analizę poezji Romana Ingardena. W przeciwieństwie do światowego rozgłosu dzieła filozoficzno-literackiego fenomenologa, jego dzieło literackie pozostaje nieznane. Zachowane w domowym archiwum, doczekało się nielicznych – jeszcze w okresie lwowskim – publikacji i niewielu lapidarnych wzmianek w poświęconych mu rozprawach, choć wiele wskazuje na to, że sam przygotował do druku wybór z juwenilnych, pisanych w latach 1909–1913 wierszy. Ułożył je w szesnastoczęściowy cykl i zatytułował podobnie jak poszczególne tworzące go części, a także dołączył późny wiersz z 1946 roku. Zarówno utwory poetyckie, jak i fragmenty prozy i dramatu oraz dziennik intymny z punktu widzenia tematyki, leksyki i stylistyki, a wiersze – także wersyfikacji, sytuują się w poetyce schyłkowo-młodopolskiej. Zarazem jednak można w nich rozpoznać przyszłe problemy nurtujące filozofa. Pod tym względem szczególnie ważne wydają się refleksje o podmiotowości, wyraziste zwłaszcza w dzienniku intymnym i niektórych częściach cyklu, ale sygnalizowane już samym jego tytułem: Sam na sam ze sobą, które można czytać jako wstęp do polemiki z Edmundem Husserlem.
Przestrzenie słowa Romana Ingradena
Keywords: archive; Young Poland; phenomenology; symbolisms; dialogical subject; scene of the mind; semantics of sounds; archiwum; Młoda Polska; fenomenologia; symbolika; podmiot dialogiczny; scena umysłu; semantyka dźwięków